Spawning activity of Oryzias woworae Parenti & Hadiaty 2010 with the Suplementation Spirulina Meal in the Diet - Mas Bayu Syamsunarno; Mustahal; Achmad Noer Faqih; Achmad Noerkhaerin Putra; Muh. Herjayanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Spirulina platensis is a feed additive that can improve the reproductive performance of fish. It has never been given to the endemic fish Oryzias woworae which can lay eggs every day. Therefore, a study was conducted that aims to examine spawning activities related to egg-laying behavior, number of eggs, and egg diameter of O. woworae. The study used a sex ratio of 1♂:1♀ in spawning. The test feeds were commercial feed (Feng Li 1) or 0% without spirulina (treatment A), the addition of spirulina 5% (treatment B), 10% (treatment C), and 20% (treatment D). Observations were made every hour for 6 days. The spawning temperature was controlled at a value of 26.6±0.2°C. The results showed differences in the behavior of O. woworae in releasing eggs on spawning days. Giving spirulina causes the behavior of releasing eggs to occur at intervals of 1-3 hours, while without spirulina, it only occurs 1 hour on spawning days. The highest number of eggs was produced by giving spirulina 20% with a diameter range of 1.35-1.37 mm. The presence of a small egg diameter in the 20% spirulina treatment indicated that an increase in the number of eggs affected the ovaries capacity, so the diameter decreased. However, the average diameter of 20% of spirulina eggs was still the same as without spirulina administration. The stable temperature at 26.6±0.2°C caused the spawning activity of O. woworae to only occur in the morning between 07:00-09:00.